Historical Perspective of Concept of Decentralization - Rawat Negi, Anju (Journal of Commerce and Trade, 2009)
Present day’s writers have so widely and differently made use of this term. In the words of Norman D. Palmer it has become less precise. Some times delegation and devolution have frequently been used instead of decentralization.Devolution may be effected either constitutionally or statutorily the former course is adopted generally in the case of federation where the powers are divided between the center and the federating autonomous units.With the march of civilization and particulary with the emergence of the concept of the welfare state, the functions of the state have multiplied. It is no longer a regulatory state as it was until the middle of the 19th Century. Today is has become a service state.